2021
DOI: 10.14309/ajg.0000000000001132
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Future Liver Abnormalities in Patients With Intrahepatic Cholestasis of Pregnancy

Abstract: INTRODUCTION:There are limited data on the incidence, predictors, and time to future liver abnormalities in patients with intrahepatic cholestasis of pregnancy (ICP). METHODS:Single-center retrospective study of pregnant women with and without ICP who delivered from 2005 to 2009 evaluating incidence and time to future liver abnormalities. Women returning for care with liver function tests at a minimum of 6 months postpartum were included. Liver disease diagnoses and liver functions test abnormalities were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Additionally, a recent study has shown that patients with ICP have an increased risk of elevated liver enzymes detected greater than 6 months postpartum and subsequent diagnosis of liver disease, most commonly non-alcoholic fatty liver disease (NAFLD). 16 Other studies have demonstrated an increased risk of gallstones, hepatitis C infection, cirrhosis, and hepatobiliary malignancies in patients with ICP, although the causality is unclear. 17,18 Patients with ICP may therefore benefit from postpartum surveillance for liver disease and screening for hepatitis C.…”
Section: Pregnancy-associated Liver Injury Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study has shown that patients with ICP have an increased risk of elevated liver enzymes detected greater than 6 months postpartum and subsequent diagnosis of liver disease, most commonly non-alcoholic fatty liver disease (NAFLD). 16 Other studies have demonstrated an increased risk of gallstones, hepatitis C infection, cirrhosis, and hepatobiliary malignancies in patients with ICP, although the causality is unclear. 17,18 Patients with ICP may therefore benefit from postpartum surveillance for liver disease and screening for hepatitis C.…”
Section: Pregnancy-associated Liver Injury Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…While ICP symptoms typically resolve postpartum, the condition can recur in future pregnancies. Additionally, a recent study has shown that patients with ICP have an increased risk of elevated liver enzymes detected greater than 6 months postpartum and subsequent diagnosis of liver disease, most commonly non‐alcoholic fatty liver disease (NAFLD) 16 . Other studies have demonstrated an increased risk of gallstones, hepatitis C infection, cirrhosis, and hepatobiliary malignancies in patients with ICP, although the causality is unclear 17,18 .…”
Section: Pregnancy‐associated Liver Injurymentioning
confidence: 99%
“…No que concerne os fatores genéticos, as mutações dos genes ABCB11, ABCB4, ABCC2, ATP8B1 e receptor farnesoide X (FXR) são os principais causadores deste agravo, encontrados em até 15% das pacientes portadoras de CIHG. Estas mutações culminam em susceptibilidade ao estrogênio e a progesterona que inibem a bomba exportadora de sais biliares dos hepatócitos (5)(6)(7) .…”
Section: Discussõesunclassified
“…The incidence of intrahepatic cholestasis of pregnancy is reported to be between 0.2% and 2% but varies widely with ethnicity and geographic location. It is most common in South America and northern Europe [8][9][10]. There is a higher incidence of intrahepatic cholestasis of pregnancy in women with a multiple pregnancy (up to 22% in one study) [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that children's food allergy may be closely related to family genetic history and abnormal maternal metabolism during pregnancy [24][25][26]. Increasingly intrahepatic cholestasis of pregnancy is recognized to be associated with an abnormal metabolic profile [9,27]. Thus, it is essential to clarify whether the incidence rate and degree neonatal food allergy worsens among pregnant women with intrahepatic cholestasis of pregnancy.…”
Section: Introductionmentioning
confidence: 99%